The Effect of Transformational Leadership on Employee Performance through Job Satisfaction and Organizational Commitment as Mediating Variables at PT Purifikasi Andalan - Musa Mujahid Haqoni; Rahmadani Nur Permanawati (Badan Penerbit STIEPARI Press, 2025)
This study examines the influence of transformational leadership on employee performance, with job satisfaction and organizational commitment serving as mediating variables, at PT Purifikasi Andalan. The research focuses on employees working in the company’s sector, where performance optimization remains a challenge despite the application of a transformational leadership style. Transformational leadership, characterized by inspiring vision, individualized consideration, intellectual stimulation, and motivational influence, is expected to drive higher performance levels by shaping employees’ attitudes and behaviors. The study aims to analyze both the direct effect of transformational leadership on employee performance and the indirect effect through the mediation of job satisfaction and organizational commitment. Job satisfaction reflects employees’ emotional response to their work, while organizational commitment indicates their loyalty and willingness to contribute to organizational goals. Both factors are hypothesized to strengthen the positive relationship between leadership and performance outcomes. A quantitative research design was employed, utilizing the Structural Equation Modeling (SEM) technique with a Partial Least Squares (PLS) approach. Data were collected through questionnaires administered to a purposively selected sample of respondents from the company’s workforce. The purposive sampling method ensured that participants had relevant experience and knowledge to provide informed responses. The findings reveal that transformational leadership exerts a positive and statistically significant influence on employee performance. Furthermore, transformational leadership has a significant positive impact on job satisfaction and organizational commitment, both of which, in turn, enhance employee performance. These mediating variables play a critical role in explaining how leadership style translates into improved work outcomes. The results suggest that fostering a transformational leadership approach, alongside initiatives to boost job satisfaction and organizational commitment, can be an effective strategy for improving overall employee performance in the organization’s specific operational context.